ANALISIS TINDAK PIDANA SENGAJA MELAKUKAN PENYERANGAN KEPADA SEORANG ATASAN (STUDI PUTUSAN NOMOR 134-K/PMT-II/BDG/AL/IX/2022): Analysis Of The Crime Of Intentionally Committing Attack On A Superior (Study Decision Number 134-K/PMT-II/BDG/AL/IX/2022) - Agung Satria Susanto; Prastopo (Faculty of Law, Universitas Trisakti, 2025)
The criminal act of insubordination within the military is a serious offense that disrupts the hierarchical structure and discipline among soldiers. This study examines the compatibility between the elements of insubordination as defined in Article 106 of the Military Criminal Code (KUHPM) and the defendant’s actions in Decision Number: 134-K/PMT-II/BDG/AL/IX/2022. The problems discussed include the elements of the military crime involving a subordinate attacking a superior, and whether the defendant’s actions, based on the legal facts in the aforementioned ruling, align with the elements of insubordination as applied by the judges. This research adopts a normative legal approach and employs qualitative analysis. The findings reveal that not all elements in Article 106 KUHPM were fulfilled, particularly the absence of physical violence, making Article 105 KUHPM more appropriate for prosecution. The study concludes that misclassification of the article led to inaccurate judicial considerations. The recommendation emphasizes the need for greater judicial precision in assessing criminal elements to ensure the achievement of substantive justice.